TINJUAN TERHADAP EFEKTIVITAS STRATEGI MANAJEMEN PENDIDIKAN DI SEKOLAH DASAR BERBASIS MBS DI PROVINSI DKI JAKARTA - Syafira, Wilda; Nazwa Azhar Aulia; Siti Keysa Ikrimah; Arita Marini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
abstract: This study focuses on the effectiveness of education management strategies in primary schools that implement School-Based Management (SBM) in DKI Jakarta Province. The background of this study is based on the need to improve the quality of education amid the challenges of globalization and technological advances. It aims to evaluate the extent to which the implementation of MBS can improve the effectiveness of education in primary schools. The method used is descriptive qualitative with a sample of several primary schools in DKI Jakarta selected through purposive sampling. The results showed that the involvement of the school community and the principal's managerial skills play an important role in the effectiveness of the implementation of SBM. Positive impacts are seen in the quality of teaching and student learning outcomes, as well as the development of teacher professionalism and parental involvement. The contribution of this study lies in a deeper understanding of the factors that influence the success of SBM in primary schools. The resulting recommendations are expected to guide decision-makers in the education sector to optimize the MBS-based education management strategy in DKI Jakarta Province.